Taylor Polynomials of the Reciprocal Gamma Function - Abdlgader M. Inbaig (The Libyan Journal of Science, 2023)
Using a Taylor Series of Reciprocal Gamma instead of a Reciprocal Gamma has the advantage, as the series and the function agree broadly around 0. The more terms we include in our approximate function, the better the approximation to the true value. reciprocal Gamma have an intersting combinatorial interpretation. The geometrical representation of the Gamma reciprocal function demonstrates how accurately the Taylor polynomials represent the actual graph of the reciprocal Gamma function. The numerical computations in this paper are achieved in aid of a MATLAB software as well as graph the Gamma function, and the reciprocal Gamma function with its Taylor approximations.